The Design of the Pilot Type Zero Steady-State Error of Water Hydraulic Overflow Valve - Luo, Jing; Zhang, Li; Zhang, Yi Bo; Yuan, Rui Bo (Applied Mechanics and Materials, 2012)
This paper studies on its cavitation and noise problem, according to traditional pressure controlling valve has a low accuracy of constant pressure, large leakage, poor lubrication, easy corrosion and so on, designs a new structure of pilot type of water hydraulic overflow valve based on the special physicochemical properties; Detecting the inlet pressure of the main valve with the help of the micro-pressure sensor and using closed-loop feedback control and dynamic pressure feedback control to eliminate steady-state error.